2017
DOI: 10.1007/s40618-017-0608-z
|View full text |Cite
|
Sign up to set email alerts
|

Does early response to intravenous glucocorticoids predict the final outcome in patients with moderate-to-severe and active Graves’ orbitopathy?

Abstract: Patients who deteriorate at 6 weeks after ivGCs are unlikely to benefit from continuing ivGCs. Patients unresponsive at 6 weeks still have a significant possibility of improvement later. Accordingly, they may continue ivGC treatment, or, alternatively, possibly stop ivGCs and be switched to a second-line treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 20 publications
3
36
0
10
Order By: Relevance
“…Overall, AITD (45)(46) represent the most frequent autoimmune endocrinopathies within the scope of PAS and are present in 70-75% of the patients [15]. AITD within PAS can occur with or without Graves' orbitopathy [45][46][47].The second most prevalent endocrine autoimmune disease in the adult PAS type is T1D with 50-60% [48]. Combination of both diseases defines PAS type III, whereas AD, essential for PAS II, occurs in 40-50% of all cases with PAS.…”
Section: Adult Pasmentioning
confidence: 99%
“…Overall, AITD (45)(46) represent the most frequent autoimmune endocrinopathies within the scope of PAS and are present in 70-75% of the patients [15]. AITD within PAS can occur with or without Graves' orbitopathy [45][46][47].The second most prevalent endocrine autoimmune disease in the adult PAS type is T1D with 50-60% [48]. Combination of both diseases defines PAS type III, whereas AD, essential for PAS II, occurs in 40-50% of all cases with PAS.…”
Section: Adult Pasmentioning
confidence: 99%
“…Using CAS, a very useful, although imperfect, tool for assessing inflammation, inactivation of TAO (final CAS ≤2/7) has been reported in about 60% of cases in 9 randomized studies and 90% of cases in 13 non-randomized studies (103). Inactivation may occur very early (within a few weeks, but even slightly later during the intravenous glucocorticoid treatment) (113). In a large randomized clinical trial of 159 patients, CAS decreased by at least two points in more than 80% of patients receiving a cumulative dose of intravenous methylprednisolone of 5 or 7.5 g and about 60% in those given a cumulative dose of 2.5 g (112).…”
Section: The Road Beyond Initial Investigation Of Biologicals -Restormentioning
confidence: 99%
“…The currently used total dose is 4.5 g of methylprednisolone, with the higher dosage of 7.5 g being slightly more effective albeit with greater toxicity [94]. Bartalena et al showed that those who deteriorate at 6 weeks after IV GCs are unlikely to benefit from continuing IV GCs as 63 % and 53 % remained in the same GO category at 12 and 24 weeks respectively [95]. In the same study, the patients who were unresponsive at 6 weeks eventually improved in 28 % of cases for composite GO index, 58 % for CAS and 32 % for quality of life, suggesting that this group still has a significant possibility of improvement later [95].…”
Section: Glucocorticoidsmentioning
confidence: 99%